2011
DOI: 10.5897/ajmr10.846
|View full text |Cite
|
Sign up to set email alerts
|

New hosts of 16SrI phytoplasma group associated with edible Opuntia ficus-indica crop and its pests in Mexico

Abstract: In Mexico in the region of Nopaltepec in Mexico State, the edible Cactus crop, Opuntia ficus-indica is mainly cultivated for prickly pear fruit production. This crop has problems with common pests (insects, mollusks and weeds) which may serve as reservoirs and together with the named Cactus with phytoplasma-like symptoms which through the time inhibit the fruit production, and for this reason, the farmers called these Opuntia plants as Planta Macho (male plant). For molecular identification of the probably inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This could have implications for propagating diseases using as seed cladodes that could contain phytoplasmas but have no visible symptoms. Fucikovsky et al (2011) also identified phytoplasmas in healthy and diseased cladodes with the symptom of inhibition of fruit production, characteristic of cactus pear "macho plants", which also exhibit thickening and heart-shaped cladodes; these symptoms have been associated with phytoplasmas of the species Candidatus Phytoplasma asteris in the 16Srl group. These phytoplasmas have been also found in other plants (Argemone mexicana and Lupinus sp.…”
Section: Identification Of Phytoplasmas Using Rflpmentioning
confidence: 95%
See 2 more Smart Citations
“…This could have implications for propagating diseases using as seed cladodes that could contain phytoplasmas but have no visible symptoms. Fucikovsky et al (2011) also identified phytoplasmas in healthy and diseased cladodes with the symptom of inhibition of fruit production, characteristic of cactus pear "macho plants", which also exhibit thickening and heart-shaped cladodes; these symptoms have been associated with phytoplasmas of the species Candidatus Phytoplasma asteris in the 16Srl group. These phytoplasmas have been also found in other plants (Argemone mexicana and Lupinus sp.…”
Section: Identification Of Phytoplasmas Using Rflpmentioning
confidence: 95%
“…), as well as in bugs (Chelinidae sp. ), which can function as reservoirs and vectors of phytoplasmas, respectively (Fucikovsky et al 2011). Therefore, it is important to control weeds and insects in areas surrounding cactus pear plantations to reduce the risk of damage by phytoplasmas, among other pathogens.…”
Section: Identification Of Phytoplasmas Using Rflpmentioning
confidence: 99%
See 1 more Smart Citation